HLA‐DRB3/4/5 mismatches are associated with increased risk of acute GVHD in 10/10 matched unrelated donor hematopoietic cell transplantation. Issue 8 (20th June 2018) - Ducreux, Stéphanie; Dubois, Valérie; Amokrane, Kahina; Yakoub‐Agha, Ibrahim; Labalette, Myriam; Michallet, Mauricette; Rubio, Marie‐Thérèse; Kennel, Anne; Forcade, Edouard; Lafarge, Xavier; Bulabois, Claude‐Eric; Masson, Dominique; et al.
Abstract: Matching for HLA‐A, ‐B, ‐C, and ‐DRB1 loci (8/8 match) is currently the gold standard for unrelated donor hematopoietic cell transplantation (HCT). In Europe, patients are also matched at the HLA‐DQB1 loci (10/10 match). However, there is increasing evidence that matching at HLA‐DRB3/4/5 loci may help to lower transplant‐related morbidity and mortality. We therefore investigated the impact of HLA‐DRB3/4/5 mismatches on outcomes in 1975 patients who received a first 10/10 matched unrelated donor (MUD) HCT in France from 2000 to 2012 for a hematological malignancy. High‐resolution typing was performed at HLA‐A, ‐B, ‐C, ‐DRB1, ‐DQB1, ‐DPB1, and ‐DRB3/4/5 loci for all donor/recipient pairs. Compared with DRB3/4/5‐matched pairs, patients who received a MUD HCT from a DRB3/4/5 mismatched donor had a significantly increased risk of grade II‐IV acute graft‐versus‐host disease (aGVHD) (Adjusted Hazard Ratio (HR) 1.43 (1.07 to 1.90)) associated with lower graft‐versus‐host disease‐free and relapse‐free survival (GRFS) (Adjusted HR 1.20 (1.02 to 1.42)). Conversely, we observed no differences in terms of chronic GVHD, nonrelapse mortality, relapse and overall survival. However, we believe that patients stand to benefit from DRB3/4/5 loci being considered for unrelated donor selection to improve GRFS and then quality of life after unrelated HCT.